Janina Korolewicz-Waydowa, debut and first stage experiences - Wąsacz-Krztoń, Jolanta (Wydawnictwo Uniwersytetu Rzeszowskiego, 2024)
This article is dedicated to the debut and early stage career of Janina Korolewicz-Wayda. The artist made her debut at the Lviv Opera as Hanna in Moniuszko’s “The Haunted Manor” (1894), and she first appeared on the stage of the Warsaw Grand Theatre as Amina in Bellini’s “La sonnambula” (1897). During the opening of the Lviv Grand Theatre, she performed the role of Bronka in Żeleński’s “Jontek” (1900), and it was also on this stage that she first sang the role of Halka in Moniuszko’s opera, a role she cherished throughout her life. Initially, she sang coloratura parts, then lyrical and dramatic ones. The initial reviews of her performances were varied, but with each season, critics increasingly appreciated her vocal and acting talent, and in later years, they only wrote about Janina Korolewicz-Wayda’s great artistry

Niniejszy artykuł został poświęcony debiutowi i początkom kariery scenicznej Janiny Korolewicz-Waydowej. Artystka debiutowała w Operze Lwowskiej jako Hanna w Strasznym dworze Moniuszki (1894 r.), na deskach warszawskiego Teatru Wielkiego po raz pierwszy wystąpiła jako Amina w Lunatyczce Belliniego (1897 r.). Podczas otwarcia Teatru Wielkiego we Lwowie wykonała partię Bronki w Jontku Żeleńskiego (1900 r.), także na tej scenie zaśpiewała po raz pierwszy rolę Halki Moniuszki, którą do końca życia darzyła szczególnymi względami. Początkowo śpiewała partie koloraturowe, potem liryczne i dramatyczne. Pierwsze recenzje dotyczące jej występów były zróżnicowane, jednak z każdym sezonem krytycy doceniali talent wokalny i aktorski, a w późniejszych latach pisano już tylko o wielkim artyzmie Janiny Korolewicz-Waydowej.
Janina Korolewicz-Waydowa, debiut i pierwsze doświadczenia sceniczne
Keywords: artistic life of Lviv; music; opera; theatre; Janina Korolewicz-Wayda; Janina Korolewicz-Waydowa; życie artystyczne Lwowa; muzyka; teatr